2002
DOI: 10.1152/physiolgenomics.00079.2002
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor gene cluster on rat chromosome 8 in nociceptive and blood pressure hyperresponsiveness

Abstract: Spontaneously hypertensive rats (SHR) exhibit enhanced pressor, heart rate, and nociceptive responses to spinal nicotinic agonists. This accompanies a paradoxical decrease in spinal nicotinic receptor number in SHR compared with normotensive rats. The congenic strain, SHR-Lx, with an introgressed chromosome 8 segment from the normotensive Brown-Norway-Lx strain (BN-Lx) exhibits reduced blood pressure. This segment contains a gene cluster for three nicotinic receptor subunits expressed in the nervous system. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…␣3, ␣5, and ␤4 subunits are encoded by a gene cluster localized to rat chromosome 8. They appear to be candidate genes for the spontaneously hypertensive rats phenotype (Khan et al, 2002). As reported in studies with dorsal root and peripheral ganglia (Keiger and Alker, 2000;Genzen et al, 2001), we identified transcripts for the five nicotinic receptor subunits in DRG neurons.…”
Section: Nicotinic Receptor Binding Sites In Rat Spinal Cordsupporting
confidence: 56%
“…␣3, ␣5, and ␤4 subunits are encoded by a gene cluster localized to rat chromosome 8. They appear to be candidate genes for the spontaneously hypertensive rats phenotype (Khan et al, 2002). As reported in studies with dorsal root and peripheral ganglia (Keiger and Alker, 2000;Genzen et al, 2001), we identified transcripts for the five nicotinic receptor subunits in DRG neurons.…”
Section: Nicotinic Receptor Binding Sites In Rat Spinal Cordsupporting
confidence: 56%
“…Peripheral and central nervous system control of cardiovascular function mediated through the autonomic nervous system is critical in homeostatic maintenance of blood pressure and responsiveness to exercise, postural alterations, and stress (Suh et al, 1936;Vargas and Brezenoff, 1988;Buccafusco, 1996;Khan et al, 2002). Central cholinergic pathways in the spinal cord and higher brain centers modulate cardiovascular responses to influence basal blood pressure and baroreflex or pressor responses via the neurotransmitter acetylcholine (ACh).…”
Section: Introductionmentioning
confidence: 99%
“…They mapped a quantitative trait locus (QTL) for blood pressure (BP) on rat chromosome 8 (Chr 8). Kren and coworkers established a congenic strain to prove that such as a QTL really existed [2][3][4]. Independently, Takami and collaborators found one locus for the peroxisamol 3-keto acyl-CoA thiolase on Chr 8 cosegregated with BP in crosses involving SHR and Dahl/Iwai salt-sensitive rats [5].…”
Section: Introductionmentioning
confidence: 99%